Effectiveness of Village Revenue and Expenditure Budget Management (APBDes) in Indonesia: Literature Review - Arif; Bahri, Efri Syamsul (Indo Consultan Energi, 2025)
This research aims to provide an overview of research into the effectiveness of Village Revenue and Expenditure Budget (APBDes) management in Indonesia. This research uses a qualitative method with a literature review study approach using Publish or Perish software to determine the distribution of research on the effectiveness of APBDes in Indonesia. The database used is Google Scholar for the period 2020 to 2022. The research results show that, on average, the APBDes in Indonesia are effectively carried out by village governments as desired by the central government, with an effectiveness level of around 85% -100%. The main obstacle faced by the village government in managing the APBDes is the limited human resources, which are technologically literate, disciplined, and competent in managing village finances.